Ottoman Millet System and its Significance to Contemporary Holistic Interreligious Dialogue - Abdullah Muslich Rizal Maulana; Sitti Amalia Musdalifah (JURNAL AT-TURAS, 2024)
The issues of religious freedom and interreligious relations have been extensively debated. While the emergence of new theories and views often leads to the destruction of religious identity, in fact, tolerance and freedom lead to a strong religious identity. The Ottoman Turkish Empire, which once oversaw a third of the world's territory, presented a system that regulated existing differences. The system, named the Ottoman millet system, allegorized its people into religious communities to make it easier for religious believers to express their religious identity. The purpose of this study is to reveal the relevance of the system to the form of interreligious dialogue and harmony that occurs in the lives of religious communities. To reveal the answer fot this research question, the researcher used the content analysis method and the qualitative-phenomenological approach by looking at the object of research based on the phenomenon of how people under the Islamic rule of Ottoman Turkey as the subject of research could coexist despite coming from different nations and religions. The result found that the Ottoman millet system was implemented successfully because of the agreement of two elements in the state, namely its citizens in carrying out their obligations and the government that gave them their citizenship rights. The level of religiosity is one of the critical factors in applying this system in that era because of a deep understanding of tolerance between religious communities.